1987
DOI: 10.1111/j.1471-4159.1987.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of [3H]Dopamine Release by Nicotine in Rat Nucleus Accumbens

Abstract: The mesolimbic system of the brain has been shown to be involved in the reward properties of a number of agents. It is possible that release of monoamines by nicotine in this brain area could be related to the pleasurable aspects related to cigarette smoking. In this investigation, the effect of nicotine on the release of [3H]dopamine in the nucleus accumbens of the rat was studied. It was shown that nicotine produced a concentration-dependent increase in [3H]dopamine release at concentrations of 0.1 microM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
2

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(49 citation statements)
references
References 29 publications
2
45
2
Order By: Relevance
“…Acute exposure to cigarette smoke and nicotine has been found to upregulate dopamine transporter mRNA in the ventral tegmental area (VTA) and substantia nigra (Li et al, 2004), and chronic exposure to cigarette smoke, more so than chronic nicotine alone, has also been found to up-regulate D 1 and D 2 receptor mRNA in the VST (Bahk et al, 2002). Additionally, many in vitro studies of the VST have reported DA release in response to nicotine (Connelly and Littleton, 1983;Marien et al, 1983;Rowell et al, 1987;Sakurai et al, 1982;Westfall et al, 1983).…”
Section: Brain Dopamine Responses To Nicotine and Smokingmentioning
confidence: 99%
“…Acute exposure to cigarette smoke and nicotine has been found to upregulate dopamine transporter mRNA in the ventral tegmental area (VTA) and substantia nigra (Li et al, 2004), and chronic exposure to cigarette smoke, more so than chronic nicotine alone, has also been found to up-regulate D 1 and D 2 receptor mRNA in the VST (Bahk et al, 2002). Additionally, many in vitro studies of the VST have reported DA release in response to nicotine (Connelly and Littleton, 1983;Marien et al, 1983;Rowell et al, 1987;Sakurai et al, 1982;Westfall et al, 1983).…”
Section: Brain Dopamine Responses To Nicotine and Smokingmentioning
confidence: 99%
“…Activation of nicotinic receptors by nicotine results in an increase in the extracellular concentration of dopamine, which is thought to mediate the rewarding effects of nicotine and maintain tobacco use in dependent individuals (Corrigall et al, 1992;Koob, 1992;Stolerman and Jarvis, 1995). Acute administration of nicotine increases dopamine release from its presynaptic terminals in the striatum in a concentration-dependent manner (Andersson et al, 1981;Dwoskin et al, 1999;Kaiser et al, 1998;Ksir et al, 1995;Pontieri et al, 1996;Rowell et al, 1987;Vezina et al, 1992;Westfall et al, 1983). Synaptic dopamine concentrations are regulated by the dopamine transporter, which transports extracellular dopamine into the presynaptic terminal.…”
Section: Introductionmentioning
confidence: 99%
“…When stimulated, they increase the neuronal firing rate and transmitter release (Hall & Turner, 1972;Goodman, 1974;Giorguieff et al, 1979;Yoshida et al, 1980;Engberg & Swensson, 1980;Balfour, 1982;Westfall et al, 1983; 1 Author for correspondence. Egan & North, 1986;Rowell et al, 1987;Mereu et al, 1987). Mecamylamine and (sometimes) (+)-tubocurarine are effective blocking agents, suggesting the coexistence of ganglionic and neuromuscular junction subtypes in the same brain area (Morley, 1981;De La Garza et al, 1987).…”
Section: Introductionmentioning
confidence: 99%